2022
DOI: 10.31234/osf.io/n34t8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Openness Relates to COVID-19 Vaccination Rates across 48 United States but Politics Trump Personality

Abstract: Does geographic variation in personality across the United States relate to COVID-19 vaccination rates? To answer this question, we combined three state-level datasets: (a) Big Five personality averages (Rentfrow et al., 2008), (b) COVID-19 vaccination rates for those receiving at least one does and fully vaccinated people (CDC, 2021a), and (c) health-relevant covariates (population density, per capita GDP, and racial/ethnic data; Webster et al., 2021). Correlations showed openness as the strongest predictor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
3
1
Order By: Relevance
“…Openness to experience has also been the most strongly associated of the Big Five with liberal political orientations [ 37 ] and individuals with such attitudes have been more likely to be COVID-19 vaccine acceptors [ 38 ]. It is possibly what explains the significantly higher scores for Openness to experience in COVID-19 vaccine acceptors in this group mirrors what has been reported elsewhere in as disparate populations as those from the USA and China [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 76%
“…Openness to experience has also been the most strongly associated of the Big Five with liberal political orientations [ 37 ] and individuals with such attitudes have been more likely to be COVID-19 vaccine acceptors [ 38 ]. It is possibly what explains the significantly higher scores for Openness to experience in COVID-19 vaccine acceptors in this group mirrors what has been reported elsewhere in as disparate populations as those from the USA and China [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 76%
“…However, the most commonly used broad personality domains such as the Big Five are only weakly and sometimes inconsistently associated with vaccination. For example, neuroticism has been linked to less and openness to more favourable stances toward vaccination [19, 21,23,24,29], but there have also been reports of openness predicting negative attitudes toward vaccination in general [58]. In our cross-sectional analyses, high neuroticism and low openness weakly predicted vaccination, but these associations were non-significant in our across-time analyses.…”
Section: Plos Onecontrasting
confidence: 54%
“…Longitudinal studies have linked vaccine hesitancy to past measurements of neuroticism but no other Big Five domain [11] and vaccine intention to pre-pandemic impulsivity and psychopathy but not altruism [28]. From the pre-pandemic variations of the Big Five, only higher openness predicted vaccination rates across 48 US states [29], whereas higher pre-pandemic neuroticism predicted vaccination rates across 56 countries [30].…”
Section: Personality Traits and Vaccination Against Covid-19: Prior E...mentioning
confidence: 99%
“…This makes understanding which factors best predict vaccination decisions in this group vitally important. Demographic characteristics (Sherman et al, 2021), attitudes toward vaccination (Breslin et al, 2021;Shacham et al, 2021), perceived social support (Moscardino et al, 2022), personality traits (Webster et al, 2022), fear of COVID-19 (Willis et al, 2021), understanding of COVID-19 (Ruiz and Bell, 2021), trust in health authorities (Petersen et al, 2021) and previous vaccination history for the seasonal influenza vaccine (Caserotti et al, 2021), have each been shown, in some way, to influence vaccine acceptance/hesitancy. Yet it is also recognized that these factors may be differently relevant for family caregivers because they are likely to be actively considering both themselves and the person for whom they provide care.…”
Section: Introductionmentioning
confidence: 99%